2022
DOI: 10.1007/s00484-022-02243-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-intensity heat events on mortality and morbidity in regions with hot, humid summers: a scoping literature review

Abstract: The objective of this study is to determine the impacts of low-intensity heat on human health in regions with hot, humid summers. Current literature has highlighted an increase in mortality and morbidity rates during significant heat events. While the impacts on high-intensity events are established, the impacts on low-intensity events, particularly in regions with hot, humid summers, are less clear. A scoping review was conducted searching three databases (PubMed, EMBASE, Web of Science) using key terms based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Heat-related impacts may already be observed at lower temperature thresholds than at the 90th percentile. This may be the case in tropical regions due to high humidity levels, or in vulnerable regions where people and systems have low capacity to cope with extreme heat (Gasparrini et al, 2015;Pasquini et al, 2020;Strathearn et al, 2022). However, CHIRTS-daily is currently only available until 2016 and therefore not usable in the context for monitoring or early warnings of heatwaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat-related impacts may already be observed at lower temperature thresholds than at the 90th percentile. This may be the case in tropical regions due to high humidity levels, or in vulnerable regions where people and systems have low capacity to cope with extreme heat (Gasparrini et al, 2015;Pasquini et al, 2020;Strathearn et al, 2022). However, CHIRTS-daily is currently only available until 2016 and therefore not usable in the context for monitoring or early warnings of heatwaves.…”
Section: Discussionmentioning
confidence: 99%
“…First, despite the advantages related to the heatwave definitions employed, humidity is not included in those. Humidity may play an important role in amplifying health impacts even at lower temperature thresholds than what would be considered climatologically extreme (Gasparrini et al, 2015;Pasquini et al, 2020;Strathearn et al, 2022). This is mainly of importance for the tropical regions of Mozambique, mostly in the north of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the use of terms "heat event" and "heat wave" is similar in the context of this paper, with "heat event" referring to a series of unusually hot days. Furthermore, low-intensity heat events are also mentioned in literature as either a single-day or a multi-day event over a temperature threshold between the 85 and 92.5th percentile (Strathearn et al, 2022). In addition, some authors classify heat waves as low-intensity, severe, and extreme (Nairn and Fawcett, 2014).…”
Section: Heat Event Analysesmentioning
confidence: 99%
“…Most tropical and subtropical areas experience long summers and short winters with extended periods of sunshine. Studies have found that the incidence of respiratory, cardiovascular and renal diseases, as well as mortality in patients with cardiovascular disease ( 2 ), were closely related to low-intensity heatwaves in tropical and subtropical humid areas ( 3 ). The Lingnan region of China, located in the east Asian monsoon region, is characterized by a subtropical monsoon oceanic climate.…”
Section: Introductionmentioning
confidence: 99%